The Implications of Understanding Contextual Hadith on Religious Radicalism (Case Study of Darus-Sunnah International Institute for Hadith Sciences) - Thohari, Fuad; Muslim, Moch. Bukhori; Zada, Khamami; Misbahuddin, Misbahuddin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
In hadith studies, many conclusions state that textual reasoning towards hadith is the main cause of intolerance and radicalism. This makes some scholars such as Yusuf al-Qardhawi and Ali Mustafa Yakub offer a more complex understanding of hadith involving asbab wurud al-hadith, al-wahdah al-maudhu'iyyah fi al-hadith, ikhtilaf al-ahadith and so on. Hadith reasoning like this is considered by some as a contextualization of hadith that will prevent someone from religious radicalism. This study wants to answer the question, to what extent does contextual reasoning in hadith prevent a person from religious radicalism? Researchers will examine the formulation of contextual hadith reasoning initiated by Ali Mustafa Yaqub in al-Thuruq al-Shahihah fi Fahm al-Sunnah al-Nabawiyyah and standards of religious radicalism initiated by LIPI in the Strategy for Anticipating Radicalism and Religious Intolerance in Indonesia. Each will be used as an independent variable and dependent variable. This research is mixed research with the type of field research. The data processing technique used is a simple regression test using the SPSS 20 program. The research object of this study is the Mahasantri Darus-Sunnah International Institute for Hadith Sciences with a total of 32 people. While the sampling system in this study is a random sample. The results of this study indicate that contextual hadith reasoning has a sig. 0.008 which is less than 0.05 so it is said to have a significant effect between contextual hadith reasoning on religious radicalism. The magnitude of the influence of this hadith reasoning itself is 21.2%. The direction of the effect is negative with a magnitude of -.643 at a constant of 69.792. This means that there is a negative relationship between contextual hadith reasoning and religious radicalism. The more contextual a person's understanding of hadith is, the further away he is from radicalism.